Changing of yeaning rates using estrus synchronization and cervico-uterinal artificial insemination in goats - Mihályfi, Sándor; Németh, Attila; Németh, Szabina (Acta Agraria Debreceniensis, 2010)
Breeding aims can be more efficiently and faster achieved by using AI. AI allows higher selection intensities for male selection, adequate genetic evaluation with efficient buck using and profitable farming. Moreover, the AI has very important advantages in animal health, especially in goats. By using our AI technology, these benefits can help the farmers in the practical life.